Stage IIIB ROS1-Positive NSCLC management: crizotinib + surgery + TCM achieves exceptionally prolonged PFS (a case report) - Zhu, Yu; Zhang, Hao; Han, Zheng-xiang; Zhu, Xu; Wang, Wan-ting; Li, Huai-yang; Zhu, Shudong; Shao, Wei (Frontiers in Pharmacology, 2026)
This article reports a case of a patient with small primary foci (11 mm*8 mm), highly malignant ROS1 fusion-positive non-small cell lung cancer (NSCLC) with mediastinal and supraclavicular lymph node metastases. After neoadjuvant crizotinib targeted therapy, the patient underwent lobectomy and lymph node dissection. Postoperatively, continuous targeted therapy combined with Traditional Chinese Medicine (TCM) adjuvant intervention achieved an extremely prolonged 62-month progression-free survival (PFS) without drug resistance or obvious side effects, compared to the median real-world PFS (rwPFS) of approximately 20 months for guideline-recommended crizotinib treatment. The last follow-up in August 2025 showed the patient remained in good survival status. This case highlights a novel strategy of neoadjuvant targeted downstaging followed by surgical resection for small-lesion, highly invasive NSCLC, as well as the potential value of integrating postoperative Chinese-Western medicine management for long-term survival and treatment tolerance.